Consumption pattern on fruits and vegetables among adults: a case of Malaysia - Othman, Khairunnisa Izzati; Abdul Karim, Muhammad Shahrim; Karim, Roselina; Mohd Adzhan, Noranizan; Abd Halim, Nurhasmilaalisa (Mediterranean Center of Social and Educational Research, 2013)
The increasing growth of expenditure on fruits and vegetables in Malaysia is related to the consumers’ health awareness and increasing spending power. However, the consumption pattern on fruits and vegetables in Malaysia is still very low in comparison with other countries. Hence, this study aims to explore fruits and vegetables purchasing behavior and its consumption pattern in Malaysia. The research was conducted among adults by using quantitative approach. Self-administered questionnaires were distributed among 1200 respondents in seven selected cities around Malaysia. Eventually, the outcomes indicated that fruits like apple, orange, banana, watermelon and papaya were the most preferred fruits; meanwhile vegetables such as chili, cabbage, cucumber, leaf mustard, tomatoes and water convolvulus were most favorable to consume by adults. Moreover, quality and nutritional contents in the fruits and vegetables set as priority factors for respondents when they were shopping for it at the markets. In conclusion, the findings will beneficially provide information for marketers to plan better promotional strategies to increase fruits and vegetables consumption among adults in Malaysia.